2012
DOI: 10.5005/jp-journals-10019-1062
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hemocompatibility of Titanium after Various Surface Treatments: An in vitro Study

Abstract: Objective To evaluate the hemocompatibility of titanium after various surface treatments. Materials and methods A total of 27 disk-shaped specimens (3 ⨯ 10.0 mm) were prepared from a cylindrical rod of medical grade titanium. The disks were divided into three groups, of which one was considered as the control (mechanical surface polished surface). The other groups being sandblasted disks and anodized disks. Surface evaluation was done for sandblasted and anodized disks with scanning electron microscope. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Increased surface roughness at the nanoscale level has been reported to enhance platelet adhesion and blood coagulation [29,39]. However, BhavanChand and co-workers [40] reported contradicting results that surface roughness does not influence platelet adhesion. On the other hand, our study showed that platelets could adhere on both surfaces with slightly more preference for the ALD-HA-coated surfaces, which had lower surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…Increased surface roughness at the nanoscale level has been reported to enhance platelet adhesion and blood coagulation [29,39]. However, BhavanChand and co-workers [40] reported contradicting results that surface roughness does not influence platelet adhesion. On the other hand, our study showed that platelets could adhere on both surfaces with slightly more preference for the ALD-HA-coated surfaces, which had lower surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study was conducted by Bhavanchand et al 4 to evaluate the titanium's hemocompatibility after surface treatment. The hemocompatibility test showed a reduction in the platelet count, but was under ISO standards, after exposing to titanium samples.…”
Section: Discussionmentioning
confidence: 99%
“…3 the implant's success rate depends on its biocompatibility and osseointegration. 4 Biocompatibility may be divided into hemocompatibility (blood) and cytocompatibility (cell and tissue). The biocompatibility depends on the survival of the cell affected by the material usage.…”
Section: Introductionmentioning
confidence: 99%